Mitf regulates gene expression networks implicated in B cell homeostasis, germinal center responses, and tolerance - Amarnani, Abhimanyu; Lopez-Ocasio, Maria; Dilshat, Ramile; Anumukonda, Kamala; Davila, Jonathan; Malakhov, Nikita; Huan, Chongmin; Magnusdottir, Erna; Steingrimsson, Eirikur; Roman, Christopher A. (Frontiers in Immunology, 2024)
The microphthalmia transcription factor Mitf has been shown to regulate B cell activation and tolerance. However, the underlying B cell-specific mechanisms responsible, and those that distinguish Mitf from closely related Mitf/TFE (MiT) transcription factors Tfe3, Tfeb, and Tfec, remain obscure. Two complementary mouse models of Mitf and MiT deficiency – the Mitfmi-vga9/mi-vga9 systemic loss-of-function mutation, and B-cell specific MiT family inactivation via transgenic expression of a trans-dominant negative (TDN) protein (TDN-B) – were used to identify MiT family candidate target genes and pathways. Both models displayed spontaneous splenomegaly coincident with elevated plasma cell numbers, autoantibody titers, and proteinuria. These abnormalities appeared dependent on T helper cells, but independent of other non-B cell intrinsic effects of systemic Mitf inactivation. MiT inactivation in B cells augmented aspects of lupus-like autoimmune disease on the C57BL/6-Faslpr/lpr background. In both models, RNAseq of ex vivo resting B cells showed transcriptional upregulation of genes that control cell cycle, germinal center responses, and plasma cell differentiation. Among the genes strongly upregulated in both models were Socs6, Isp53 (Baiap1), S1pR2, and IgG2b/c. Mitf null B cells, but not TDN-B cells, showed evidence of type I interferon dysregulation implicating B-lymphocyte non-autonomous mechanisms caused by systemic absence of Mitf. These studies clarify Mitf's role as 1) a key regulator of a B cell intrinsic germinal center program that influences self-tolerance through novel target genes, and 2) a regulator of systemic inflammatory processes that can impact the B cell microenvironment.